Ramifications of debt restructuring on the Euroa area: The example of large European economies' exposure to Greece - Ansgar Belke; Christian Dreger (Intereconomics, 2011)
The Greek government budget situation plays a central role in the debt crisis in the euro area. Strong consolidation measures need to be implemented, with potential adverse effects on the Greek economy and further credit requirements. Debt conversion might therefore become a reasonable alternative. The following paper provides some simulation-based calculations of the expected fiscal costs for the governments in the large European countries, Germany, France, Spain and Italy, arising from different policy options - among them a second Greek rescue package.
Keywords: 330